PEMANFAATAN MANAJEMEN PEMBELAJARAN AUGMENTED REALITY DALAM MENDUKUNG PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) - Kasim, M. Habibi; Imtiyaz, Muhammad Farisal; Nur, Siti; Rohman, Aa Abdul; Abdul Rohim, Adi (STKIP PGRI Situbondo, 2024)
The boredom in the teaching and learning process is very much felt, especially in the new normal era. This is felt by both lecturers and students. So that an effective and interesting learning media is needed in its delivery, of course the lecturers think hard about the right solution so that the material is conveyed and students can understand it. Augmented Reality (AR) is one of the interactive media in learning, its appearance in the form of 3D objects, as well as sound and image improvisation that supports it, is expected to be interesting and fun in learning, especially at Nusantara Islamic University. It is hoped that this method can answer